Prevalencia de la queratoconjuntivitis seca canina (QCSC) durante el periodo comprendido de febrero a junio en la clínica veterinaria mundo animal en la cuidad de cali . (2021)
Canine keratoconjunctivitis sicca (QCSC) is a common eye disease in the dog characterized by chronic inflammation of the lacrimal glands, cornea, and conjunctiva, leading to impaired tear production and excessive mucous secretion. Its etiology is not specific, but the immunemediated form is indicated as the most common. The Schirmer test helps us to measure tear production by establishing a value in millimeters of 0 - 35 with the tear filling that our patient is producing, from here we interpret that in one minute if there is a filling of 0 - 5 mm it is a QCSC , 6 to 10 is a moderate QCSC, that of 10 - 15 mm is a suspected patient to suffer from the disease and that of 15 - 25 mm onwards is a normal tear production (Flores, et al. Hinostroza, et al. Grandez, et al. Canales & Serrano. 2013) (Cabrera, et al. Gaitán, et al. Escobar. 2017), in this way; With the Schirmer test, 50 randomly chosen canine patients were diagnosed from one year of age who entered the animal world veterinary clinic located in Cali, of which their respective owners granted us authorization to perform the test during the period of February to June 2021.